Mast Cell Distribution in Human Carotid Atherosclerotic Plaque Differs Significantly by Histological Segment. (November 2021) - Mekke, Joost M.; Egberts, Daan H.J.; Waissi, Farahnaz; Timmerman, Nathalie; Bot, Ilze; Kuiper, Johan; Pasterkamp, Gerard; de Borst, Gert J.; de Kleijn, Dominique P.V.
Abstract : Objective: Mast cells (MCs) are important contributors to atherosclerotic plaque progression. For prospective studies on mast cell contributions to plaque instability, the distribution of intraplaque MCs needs to be elucidated. Plaque stability is generally histologically assessed by dividing the plaque specimen into segments to be scored on an ordinal scale. However, owing to competitive use, studies may have to deviate to adjacent segments, yet intersegment differences of plaque characteristics, especially MCs, are largely unknown. Therefore, the hypothesis that there is no segment to segment difference in MC distribution between atherosclerotic plaque segments was tested, and intersegment associations between MCs and other plaque characteristics was investigated. Methods: Twenty-six carotid atherosclerotic plaques from patients undergoing carotid endarterectomy included in the Athero-Express Biobank were analysed. The plaque was divided in 5 mm segments, differentiating between the culprit lesion (segment 0), adjacent segments (–1/+1) and more distant segments (–2/+2) for the presence of MCs. The associations between the intersegment distribution of MCs and smooth muscle cells, macrophage content, and microvessel density in the culprit lesion were studied. Results: A statistically significant difference in MCs/mm 2 between the different plaque segments ( p < .001) was found, with a median of 2.79 (interquartile range [IQR] 1.63 – 7.10) for the culprit lesion, 1.34 (IQR 0.26 – 4.45) for the adjacent segment, and 0.62 (0.14 – 2.07) for the more distant segment. Post hoc analyses showed that intersegment differences were due to differences in MCs/mm 2 between the culprit and adjacent segment ( p  = .037) and between the culprit lesion and the more distant segment ( p < .001). MCs/mm 2 in multiple different segments were positively correlated with microvessel density and macrophage content in the culprit lesion. Conclusion: MC numbers reveal significant intersegment differences in human carotid plaques. Future histological studies on MCs should use a standardised segment for plaque characterisation as plaque segments cannot be used interchangeably for histological MC analyses.